2022
DOI: 10.3390/ma15217784
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Compression Mechanical Properties of Polyoxymethylene-Fiber-Reinforced Concrete

Abstract: The excellent overall performance of polyoxymethylene (POM) fiber enables it to show great potential for engineering applications. The effect of POM fibers on the dynamic compression mechanical properties of concrete is an important issue for its application in engineering structures such as airport pavement and bridges. It is necessary to investigate the dynamic compressive mechanical properties of POM-fiber-reinforced concrete (PFRC) under impact loading. The PFRC specimens with various POM fiber lengths (6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…POM fiber in UHPC bridges cracks and restrains the matrix, which can enhance the material's toughness to avoid stress concentration due to the blocking of shock waves [37]. POM fiber can also inhibit the emergence and expansion of cracks, reducing the wear and tear of the material, thus improving the impact resistance and abrasion resistance of UHPC.…”
Section: Effect Of Pom Fiber Content On Impact and Abrasion Resistancementioning
confidence: 99%
“…POM fiber in UHPC bridges cracks and restrains the matrix, which can enhance the material's toughness to avoid stress concentration due to the blocking of shock waves [37]. POM fiber can also inhibit the emergence and expansion of cracks, reducing the wear and tear of the material, thus improving the impact resistance and abrasion resistance of UHPC.…”
Section: Effect Of Pom Fiber Content On Impact and Abrasion Resistancementioning
confidence: 99%
“…Many earlier investigations on the dynamic characteristics of concrete have been conducted, including the dynamic compression mechanical properties of polyoxymethylene-fiber-reinforced concrete [8]. Dynamic properties test and constitutive study of lightweight aggregate concrete under uniaxial compression [9].…”
Section: Introductionmentioning
confidence: 99%
“…One way to reduce the cost of PVA-ECC is to partially replace the high-cost oiled PVA with relatively low-cost fibers. It has been shown that blending PVA fibers with PET fibers [ 25 ], PP fibers [ 26 , 27 ], steel fibers [ 28 , 29 ], and POM fibers [ 30 ] can effectively reduce the cost. Wang et al [ 31 , 32 ] showed that the incorporation of recycled steel fibers or short-cut steel wool fibers could improve the compression and tensile strengths but reduce the tensile strain capacity.…”
Section: Introductionmentioning
confidence: 99%